2012
DOI: 10.1536/ihj.53.23
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coronary CT Angiography in Asymptomatic Patients With Type 2 Diabetes Mellitus

Abstract: SummaryDiabetic patients with coronary artery disease are often asymptomatic, making appropriate care of such patients difficult. The purpose of this study was to investigate the prevalence of coronary lesions in asymptomatic diabetic patients. Coronary computed tomography (CT) angiography was performed in 120 consecutive diabetic patients (90 of whom were men, mean age 65, mean HbA1c 7.2%). Images from patients whose coronary artery calcium scores (CAC scores) were less than 400 were subjected to stenosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…Several studies showed that zero CAC could not rule out the presence of CAD. 23,24 In our population with a zero Agatston score, diabetic patients had a threefold higher prevalence of noncalcified plaque compared with nondiabetic patients (Figure 2).…”
Section: Discussionmentioning
confidence: 82%
“…Several studies showed that zero CAC could not rule out the presence of CAD. 23,24 In our population with a zero Agatston score, diabetic patients had a threefold higher prevalence of noncalcified plaque compared with nondiabetic patients (Figure 2).…”
Section: Discussionmentioning
confidence: 82%
“…Kamimura et al evaluated 120 consecutive diabetic patients (75% male, mean age 65) by CCTA. Significant stenosis (defined as coronary artery stenosis > 70%) was present in 5% of patients whose CAC score = 0 [47]. Min et al showed that nearly one third of asymptomatic diabetics with a CAC score of zero indeed have atherosclerosis, and that over 10% of these individuals have obstructive CAD by CCTA.…”
Section: Prevalance Of Coronary Atheroscelerosis By Ct Angiogrsphymentioning
confidence: 99%
“…Hypertension (HT), diabetes mellitus (DM) and dyslipidemia (DL) have been identified as risk factors for coronary artery disease (CAD) or the progression of vulnerable plaques [1][2][3][4]. Rupture of vulnerable plaques followed by severe stenosis of coronary arteries result in acute coronary syndrome [2].…”
Section: Introductionmentioning
confidence: 99%